1997
DOI: 10.1210/jc.82.6.1799
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Factor 1 Messenger Ribonucleic Acid Expression in Steroidogenic and Nonsteroidogenic Human Tissues: Northern Blot and in Situ Hybridization Studies

Abstract: Steroidogenic factor-1 (SF-1), a tissue-specific orphan nuclear receptor, regulates the genes of several steroidogenic enzymes, Mullerian inhibiting substance, and the gonadotrophins. Also, this transcription factor is crucial for hypothalamic, adrenal, and gonadal organogenesis in the mouse. We recently cloned the human SF-1 (hSF-1) complementary DNA (cDNA) and now report the distribution of this factor's messenger RNA (mRNA) in human tissues. Northern blot analyses of peripheral tissues revealed high hSF-1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 0 publications
6
41
1
Order By: Relevance
“…4). This finding is consistent with previous reports in humans and rats (Ramayya et al, 1997;Morohashi et al, 1999). In carp, SF-1 mRNA is only expressed abundantly in the liver of females, but not in males (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…4). This finding is consistent with previous reports in humans and rats (Ramayya et al, 1997;Morohashi et al, 1999). In carp, SF-1 mRNA is only expressed abundantly in the liver of females, but not in males (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In endocrine cells, we and others have shown that the nuclear receptors NR5A1 and NR5A2 are important transcriptional partners for GATA4 (Viger et al 2008). Although NR5A1 is expressed in the heart, at least at the transcript level (Ramayya et al 1997, Nishimura et al 2004, there is currently no evidence for a functional role for this receptor as a transcriptional partner for GATA4 in this tissue. Unlike TBX5 in the heart (Garg et al 2003), the functional synergism between the G295S mutant and its gonadal partners NR5A1 and NR5A2 was not compromised (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SF-1 is expressed in tissues involved in steroid hormone production and reproductive function, i.e. the three layers of the adrenal cortex, testicular Leydig and Sertoli cells, ovarian interstitium, theca and granulosa cells, and, to a lesser degree, corpus luteum Ikeda et al, 1993;Morohashi et al, 1994;Ramayya et al, 1997;Morohashi, 1999). SF-1 is also expressed in non-steroidogenic tissues like pituitary gonadotropes.…”
Section: Expressionmentioning
confidence: 99%
“…SF-1 is also expressed in non-steroidogenic tissues like pituitary gonadotropes. It is also expressed in the dorsomedial portion of the ventromedial hypothalamus (VMH) Shinoda et al, 1995), in the endothelial linings of the venous sinuses and pulp veins in the spleen (Ramayya et al, 1997;Morohashi et al, 1999), and in a subset of hippocampal neurons. It has been described that in developing human embryos SF-1 represents the earliest marker of adrenogonadal differentiation, first appearing in the urogenital ridge Morohashi et al, 1995;Hanley et al, 1999;Hanley et al, 2001).…”
Section: Expressionmentioning
confidence: 99%